2017
DOI: 10.1140/epjc/s10052-016-4496-8
|View full text |Cite
|
Sign up to set email alerts
|

Stacked search for time shifted high energy neutrinos from gamma ray bursts with the Antares neutrino telescope

Abstract: A search for high-energy neutrino emission correlated with gamma-ray bursts outside the electromagnetic prompt-emission time window is presented. Using a stacking approach of the time delays between reported gammaray burst alerts and spatially coincident muon-neutrino signatures, data from the Antares neutrino telescope recorded between 2007 and 2012 are analysed. One year of public data from the IceCube detector between 2008 and 2009 have been also investigated. The respective timing profiles are scanned for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The analysis presented in this work is based on a likelihood ratio test, widely used in neutrino astronomy, e.g. in the search for neutrinos from individual point-like or extended sources by ANTARES [28,29,30,31]. It is adapted here to a full-sky search where the signal map is built according to the reference models mentioned above.…”
Section: Search Methodsmentioning
confidence: 99%
“…The analysis presented in this work is based on a likelihood ratio test, widely used in neutrino astronomy, e.g. in the search for neutrinos from individual point-like or extended sources by ANTARES [28,29,30,31]. It is adapted here to a full-sky search where the signal map is built according to the reference models mentioned above.…”
Section: Search Methodsmentioning
confidence: 99%
“…This analysis relies on a likelihood ratio test, similar to the one used in the search for neutrinos from individual point-like or extended sources by ANTARES [14,15,16,17]. It is adapted here to a full-sky search where the signal map is built according to the reference models mentioned above.…”
Section: Search Methodsmentioning
confidence: 99%
“…Assuming that a GRB and the corresponding neutrino burst are produced at the same time or within a short period, a significant delay would indicate that the electromagnetic and neutrino signals have travelled at different speeds. Note, however, that the recent experimental studies show only faint neutrino signals associated with GRB [2,3], and hence the observed delays may be inaccurate.…”
Section: Introductionmentioning
confidence: 91%
“…Those events may also produce high-energy cosmic rays and consequently bursts of high-energy neutrinos [1]. Neutrino bursts have been observed to be shifted in time with respect to the GRB (see [2,3] and references therein). The time window = − between the arrival times of a GRB and a neutrino burst can vary between an hour or several days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation